Customer data and privacy the insights you need from harvard business review - Review, Harvard Business (Gildan Audio, 2020)
Is it possible to take advantage of the benefits of data collection-and mitigate risks-for both companies and customers'Most consumers are not very skilled at evaluating privacy risks; they're either unable to determine the cost of sharing personal data online or unaware of what they're sharing. (Doesn't everyone scroll down without reading to click "I accept"') Without much intervention from most federal or state-level governments, companies are on their own to define what qualifies as reasonable use. In today's digital surveillance economy, there are no clear-cut best practices or guidelines. Gathering and using information can help customers-we see that in personalization and autofill of online forms. But companies must act in the best interest of their customers and treat the sensitive information users give them with the ethical care of doctors, lawyers, and financial advisers. The challenges of operating in a digital ecosystem aren't going away. Customer Data and Privacy: The Insights You Need from Harvard Business Review will help you understand the tangled interdependencies and complexities and develop strategies that allow your company to be good stewards, collecting, using, and storing customer data responsibly.